2000
DOI: 10.2527/2000.782380x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical infection with the nematode Trichostrongylus colubriformis increases gastrointestinal tract leucine metabolism and reduces availability of leucine for other tissues.

Abstract: Gastrointestinal (GI) tract leucine metabolism was measured in 6- to 9-mo-old lambs subjected to trickle infection with Trichostrongylus colubriformis larvae and in separate animals that were not infected. Animals prepared with a jejunal catheter and with indwelling catheters into the aorta and the portal- (PDV) and mesenteric- (MDV) drained viscera were infused simultaneously with [1-13C] and [5,5,5-2H3] leucine to determine GI tract sequestration of leucine from arterial and luminal amino acid pools by trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
59
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 25 publications
(61 reference statements)
12
59
1
Order By: Relevance
“…Possible reasons for the discrepancies between the current study and previous studies with respect to DM flow at the ileum (Gregory et al, 1985), N flow (Poppi et al, 1986;Kimambo et al, 1988) and intestinal absorption (Yu et al, 2000) may be due to the infection procedure used, namely the short-term dose in the current study and the trickle dose methods used by these authors. It is likely that the damage caused by the larvae could affect the ability of the intestine to transport AA.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…Possible reasons for the discrepancies between the current study and previous studies with respect to DM flow at the ileum (Gregory et al, 1985), N flow (Poppi et al, 1986;Kimambo et al, 1988) and intestinal absorption (Yu et al, 2000) may be due to the infection procedure used, namely the short-term dose in the current study and the trickle dose methods used by these authors. It is likely that the damage caused by the larvae could affect the ability of the intestine to transport AA.…”
Section: Discussioncontrasting
confidence: 85%
“…This suggests an increase in AA disappearance from the small intestine of the infected lambs, although the apparent absorption from the small intestine and net flux of AA across the MDV were similar between treatments. The net flux of AA across the MDV in the current study (1 to 5 g/day) is similar to the 4 to 6 g/day reported by MacRae et al (1997b) at similar intakes, but the similar net fluxes of AA across the MDV between control and parasitised lambs contrast with the observations for leucine by Yu et al (2000). While mesenteric plasma flows are within the ranges in the literature for sheep at a similar age and DM intake (700 to 1000 ml/min; Janes et al, 1985;MacRae et al, 1997b;Yu et al, 2000;Bermingham et al, 2007b), they are highly variable (CV of 28% to 40% in the control and parasitised lambs, respectively), and this variability may have masked any effects of infection on MDV AA fluxes.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations